O direito fundamental à autodeterminação informativa ante o direcionamento de conteúdos nas redes sociais - Simeão, Larissa Queiroz (2022)
The world is in continuous transformation. The development of today's social relations encompasses a reality in constant connection, in which technology acts on information. We live the transition to the digital paradigm. The sociotechnical standard is that of a networked, interactive and informational society, in which human relations are carried out simultaneously in the online and offline worlds, with emphasis on interaction through social networks. On the smartphone screen, relationships dematerialize in predictive apps such as facebook and instagram. The communicational technological infrastructure does not work only as a technique, as it has become a new perspective of thinking about the human. Every click in the virtual world leaves a digital trail. In this datafied society, data is a form of manifestation of human personality and, therefore, works as fuel for technologies while being used to individualize behaviors and monetize them, and the methods used for this are still opaque. Based on these assumptions, this research will address the right to control the use of personal data in the face of directing content on social networks based on the collection of this data by the private companies that control these virtual environments, while questioning whether the legal system homeland has adequately safeguarded the right to informational self-determination of social network users. Using a hypothetical-deductive method of approach, the study will begin with an analysis of the relationship between society and technology, and then focus on the specific objective related to the analysis of informative self-determination and the rules on the subject. Finally, based on a more skeptical philosophical current of the internet, it will bring an epistemological reflection on technology as a catalyst for social transformations, as well as on the algorithmization of relationships, the formation of filter bubbles, the paradigm of consent and how this can affect the free development of the personality.